The Importance of Diversity and Inclusiveness in Academia: Perspectives from University of The Bahamas Faculty - Sairsingh, A. Marie; Ulentin, Anne; Hall Campbell-Dean, Niambi; Curry, Christopher E.; Ellefritz, Richard G. (International Journal of Bahamian Studies, 2020)
At the recent University of The Bahamas Faculty Seminar (2020), a panel presented on the topic, “The Importance of Diversity and Inclusiveness in Academia.” Their reflections on this critical discourse foreground various facets of the subject as it relates to the Bahamian context and to the University of The Bahamas, more specifically. Over the past several decades in North America and elsewhere, emphasis on diversity and inclusiveness has been driven by the need to address issues of inequity, marginalisation, invisibility, and injustice and has, in significant ways, energized the restructuring of academic programs, shaped new pedagogical approaches, impacted university hiring practices, revised university policies, and transformed campus life.